Intestinal Microflora in Children: from Formation Disturbances Prophylaxis to Preventing Non-Infectious Diseases - D. V. Pechkurov; T. V. Turti; I. A. Belyaeva; A. A. Tjazheva (Union of pediatricians of Russia, 2016)
The article presents an overview of modern Russian and foreign scientific literature, which summarizes data on the value of normal intestinal microflora formation, and on the formation of normal microbiocenosis in ontogeny features. The causes of microbiota formation lesions and their impact on child health are described. Relevant data on the effectiveness of pre- and probiotics in the prophylaxis of noninfectious diseases is given.